2015
DOI: 10.1103/physrevlett.115.027001
|View full text |Cite
|
Sign up to set email alerts
|

Topological Crystalline Superconductivity in Locally Noncentrosymmetric Multilayer Superconductors

Abstract: Topological crystalline superconductivity in the locally non-centrosymmetric multilayer superconductors (SCs) is proposed. We study the odd-parity pair-density wave (PDW) state induced by the spin-singlet pairing interaction through the spin-orbit coupling. It is shown that the PDW state is a topological crystalline SC protected by a mirror symmetry, although it is topologically trivial according to the classification based on the standard topological periodic table. The topological property of the mirror subs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 47 publications
1
63
0
Order By: Relevance
“…11) When the multipole moment is appropriately defined, ferroic odd-parity multipole order is accompanied by spontaneous global inversion symmetry breaking. The odd-parity toroidal order was demonstrated in LiCoPO 4 , 12,13) and magnetic quadrupole order has recently been implied in Sr 2 IrO 4 . 14,15) In this paper, we focus on the odd-parity EO state and clarify the thermodynamic stability in the bilayer Rashba system.…”
Section: Introductionmentioning
confidence: 93%
“…11) When the multipole moment is appropriately defined, ferroic odd-parity multipole order is accompanied by spontaneous global inversion symmetry breaking. The odd-parity toroidal order was demonstrated in LiCoPO 4 , 12,13) and magnetic quadrupole order has recently been implied in Sr 2 IrO 4 . 14,15) In this paper, we focus on the odd-parity EO state and clarify the thermodynamic stability in the bilayer Rashba system.…”
Section: Introductionmentioning
confidence: 93%
“…On the other hand, the mechanisms and properties of odd-parity superconductivity in spin-orbit-coupled systems have been less explored until recently. In the last few years, a number of theoretical and numerical studies have shown that in the presence of strong spin-orbit interaction, odd-parity pairing can be realized in a broad range of materials without proximity to magnetic instabilities [6][7][8][9][10][11][12][13].…”
mentioning
confidence: 99%
“…We stress again that our proposal is very different from those proposed in Refs. [27,29] where a layer-dependent SO coupling produces the PDW superfluid. Our scheme, which utilizes a layer-independent SO coupling, has the advantage of simplicity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the PDW state investigated in Ref. [27] is protected by mirror symmetry in a tri-layer system, and a pair of non-trivial chiral edge excitations emerge as long as the protecting symmetries are not broken. Thus the PDW states provide an ideal experimental candidate in the search of symmetry-protected topological phases for interacting fermions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation